Plagues of the mind the new epidemic of false knowledge - Thornton, Bruce S. (ISI Books, 1999)
"Part One traces the historical and cultural roots of such ancient myths as the Golden Age and the Noble Savage and discusses the present corruption of mind wrought by those beliefs in the media and education. Part Two examines in detail three popular specimens of false knowledge; romantic environmentalism, Noble-Savage Indianism, and the Old Europe Mother Goddess". -- Jacket.
Keywords: Misvattingen; Pseudowetenschap; Reason; Truthfulness and falsehood; Wahrheit; Irrtum